2019
DOI: 10.1101/790501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Membrane stiffness is a key determinant of E coli MscS channel mechanosensitivity

Abstract: 41Prokaryotic mechanosensitive (MS) channels have an intimate relationship with 42 membrane lipids. Membrane lipids may influence channel activity by directly 43 interacting with bacterial MS channels or by influencing the global properties of the 44 membrane such as area stretch and bending moduli. Previous work has implicated 45 membrane stiffness as a key determinant of the mechanosensitivity of E. coli (Ec)MscS. 46 Here we systematically tested this hypothesis using patch fluorometry of azolectin 47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Modulators can act indirectly on MS channels, such as through the modification of the physical or chemical properties of the membrane. A decrease in membrane thickness was shown to lower the activation threshold of EcMscL, while decreased membrane fluidity hampered EcMscS gating (Perozo et al, 2002;Nomura et al, 2012;Xue et al, 2020). An atomistic MD study showed that the thickness-dependent gating of MscL is likely to be driven by the hydrophobic matching of the protein to the thickness of the bilayer, largely through the interaction of F78 (TbMscL) with the membrane surface on TM2 (Katsuta et al, 2019).…”
Section: Modulation Of Mscl Via Membrane Properties and Componentsmentioning
confidence: 99%
“…Modulators can act indirectly on MS channels, such as through the modification of the physical or chemical properties of the membrane. A decrease in membrane thickness was shown to lower the activation threshold of EcMscL, while decreased membrane fluidity hampered EcMscS gating (Perozo et al, 2002;Nomura et al, 2012;Xue et al, 2020). An atomistic MD study showed that the thickness-dependent gating of MscL is likely to be driven by the hydrophobic matching of the protein to the thickness of the bilayer, largely through the interaction of F78 (TbMscL) with the membrane surface on TM2 (Katsuta et al, 2019).…”
Section: Modulation Of Mscl Via Membrane Properties and Componentsmentioning
confidence: 99%